The Practicality of OR-IPA Learning Model to Improve Critical Thinking Skill of Prospective Physics Teachers - Binar Kurnia Prahani; Budi Jatmiko; Zainal Arifin Imam Supardi; Munasir M; Utama Alan Deta; Rosyid Althaf; Saiyidah Mahtari (Berkala Ilmiah Pendidikan Fisika, 2019)
The Indonesian National Qualification Framework in higher education requires universities to develop a curriculum that makes students have superior competence with a variety of skills that are in line with the demands of the 21st century, including Critical thinking skills. The main objective of this research is to analyze the practicality of the OR-IPA learning model, which has been developed by design to improve the critical thinking skill of prospective physics teachers on the fundamentals of physics courses. The subject of practical observations was a physics lecturer who used the OR-IPA learning model. The observation sheet of the OR-IPA learning model practicality has been declared valid and reliable by the validators. The data analysis technique uses descriptive qualitative. The results showed that the OR-IPA learning model to improve the critical thinking skill of prospective physics teachers was considered practical (3.69). Lecturers and students can use the OR-IPA learning model without significant obstacles. This research implies that the OR-IPA learning model can be an alternative to improve the critical thinking skill of prospective physics teachers in the fundamentals of physics courses.